Peningkatan Prestasi Belajar Siswa Pada Mata Pelajaran Al –Qur’an Hadits Melalui Model Menulis Puisi Pada Siswa Kelas V MI Bustanul Athfal Desa Pojok Kecamatan Garum Kabupaten Blitar - Mustarikoh; Bustanul Arifin (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
This study aims to improve student learning achievement in the subject of the Qur'an Hadith at MI Bustanul Athfal Pojok District of Garum, Blitar Regency in the academic year 2019/2020 with realistic models and poetry media. The form of this research is Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of four phases: planning, implementation, observation, and reflection. The subjects of the study were fifth-grade students of MI Bustanul Athfal Pojok, Garum sub-district, Blitar district, totalling 19 students consisting of 8 male students and 11 female students. Data sources come from teachers and students. Data collection techniques used were interviews, observation, tests, and documentation. The results of the study carried out the initial conditions before student learning increased only reached mastery of 8 students (42.1%), while 11 students (57.89%) had not yet reached accuracy with an average value of 65. In the first cycle, a realistic model and media of poetry were implemented increasing student learning outcomes reached the completeness limit of 8 students (42.1%), while 11 students (57.89%) had not reached accuracy with an average value of 69.86. At this stage, the second cycle of 19 students who achieved mastery of 18 students (94.73%) who had not completed 1 student (5.26%) and the average value of KKM science subjects was 74.79. Judging from the improvement cycle I and cycle II can conclude that this research was successful and does not need to continue the next cycle.